2011
DOI: 10.1007/s10337-011-2072-9
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolites of Isoliquiritigenin in Wistar Rats using UHPLC–TOF–MS-based Xenometabolomics

Abstract: Isoliquiritigenin, a chalcone found in licorice root and many other plants, has shown potential antioxidant, estrogenic and antitumor activities. The present study was to investigate urinary metabolism of isoliquiritigenin in Wistar rats by ultra-high pressure liquid chromatography coupled to electrospray ionization TOF-MS (UHPLC-TOF-MS)-based xenometabolomics. Urine samples were collected before and after oral administration of isoliquiritigenin, and analyzed by UHPLC-TOF-MS. After deconvolution, the resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Among them, the parent drug (M0), liquiritigenin (M2) and isoliquiritigenin (M3) were conrmed by comparison with reference standards, and the other 74 metabolites were indentied according to the obtained MS/MS data. Comparing with the previous literatures, 8,19 27 potential new metabolites of liquiritin in rats including M4, M5-M12, M20, M32, M33, M51-M58 and M70-M76 were rst tentatively identied by the UHPLC-FT-ICR-MS method in this study (ESI table †).…”
Section: Metabolic Prole Analysis Based On Uhplc-ft-icr-mssupporting
confidence: 58%
“…Among them, the parent drug (M0), liquiritigenin (M2) and isoliquiritigenin (M3) were conrmed by comparison with reference standards, and the other 74 metabolites were indentied according to the obtained MS/MS data. Comparing with the previous literatures, 8,19 27 potential new metabolites of liquiritin in rats including M4, M5-M12, M20, M32, M33, M51-M58 and M70-M76 were rst tentatively identied by the UHPLC-FT-ICR-MS method in this study (ESI table †).…”
Section: Metabolic Prole Analysis Based On Uhplc-ft-icr-mssupporting
confidence: 58%
“…To date, the superficially porous particle technology have been already applied to the determination of few drugs and metabolites in biological fluids, including whole blood, plasma, urine, or saliva [68][69][70], but up to now, no multi-target screening procedures based on this technology has been proposed. Nevertheless, this technology is plainly appropriate for the development of HPLC-MS multi-target screenings with improved performance but without the need of specific instruments compatible with pressures up to ca.…”
Section: Uhplc Technologymentioning
confidence: 99%
“…The main fragmentation pathways and MS/MS spectra are presented in Figure S3, and the combined selected ion chromatograms of BVC and its metabolites are shown in Figure S4 absorption wavelengths at 275 and 320 nm, whereas that of M1 was at 375 nm. Related studies (Legette et al, 2012;Nikolic, Li, Chadwick, Pauli, & van Breemen, 2005;Tan et al, 2011) have revealed that flavonoids can convert into the corresponding isomer of chalcone both in vivo and in vitro. The UV absorption wavelength of M1 was in accordance with the characteristic UV absorption wavelength of chalcone.…”
Section: Structure Elucidation Of Metabolitesmentioning
confidence: 99%